МЕЖДИСЦИПЛИНАРНЫЙ ПОДХОД К ДИАГНОСТИКЕ И ЛЕЧЕНИЮ ВОЗРАСТНОГО ГИПОГОНАДИЗМА, АССОЦИИРОВАННОГО С СЕРДЕЧНО-СОСУДИСТЫМИ ЗАБОЛЕВАНИЯМИ - Г. Г. Шарвадзе; Е. А. Поддубская; М. Н. Мамедов (SINAPS LLC, 2014)
Article deals with age-related hypogonadism in men as an interdisciplinary problem. Current definition, prevalence, analyzes the relationship between age and the incidents of hypogonadism were shown. The detailed overview of clinical studies, metaanalysis of causal link of androgen deficiency and erectile dysfunction, ischemic heart disease, arterial hypertension, dyslipidemia, and diabetes mellitus was presented. To date was found the relationship between metabolic syndrome and androgen deficiency. Low level of testosterone is closely connected with low libido as well as insulin resistance, abdominal obesity, dyslipidemia. Insulin resistance and hyperinsulinemia are noticed in patients with hypogonadism in comparison with obese and normal-weight patients. Therefore, metabolic risk factors are the connecting link of cardiovascular diseases and androgen deficiency. Meta-analysis of clinical trials of the effects of testosterone replacement therapy and safety of long term use was presented in the article. The article discusses the importance of a unified approach to the diagnosis and treatment of androgen-deficient conditions and cardiovascular disease.